1998
DOI: 10.1007/s002469900326
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Infarction in a 14-Year-Old Girl, Ten Years After Surgical Correction of Congenital Coronary Artery Fistula

Abstract: Acute myocardial infarction developed in a 14-year-old girl, ten years after surgical repair of a coronary artery fistula. Angiography revealed fresh thrombus in the left anterior descending branch of the left coronary artery. The thrombus probably developed in the residual cul-de-sac of the occluded fistula. A procedure to abolish the cul-de-sac was then performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The eventual goal of treating CAF is to provide long‐term event‐free survival. Conversely, several case reports and long‐term studies continue to report adverse coronary events such as discrete stenosis, acute and chronic thrombosis causing myocardial infarction and perfusion defects with traditional management . Cheung et al to date has the most extensive follow‐up data; 21 of 41 patients underwent coronary angiograms and all were asymptomatic on follow‐up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The eventual goal of treating CAF is to provide long‐term event‐free survival. Conversely, several case reports and long‐term studies continue to report adverse coronary events such as discrete stenosis, acute and chronic thrombosis causing myocardial infarction and perfusion defects with traditional management . Cheung et al to date has the most extensive follow‐up data; 21 of 41 patients underwent coronary angiograms and all were asymptomatic on follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients are asymptomatic early after CAF closure. More detailed follow‐up studies, however, have identified post CAF closure sequelae including persistent coronary dilatation , residual leak , thrombosis with or without myocardial infarction , coronary stenosis with perfusion defects , and rarely death . The risk factors for early or late coronary events have not been adequately evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Hiraishi et al., 12 reported follow‐up catheterizations including intravascular ultrasound (IVUS) on 3 patients following surgical repair of coronary fistula and reported areas of coronary artery stenosis and irregularities in the vessel wall due to intimal thickening at the site of the regressed coronary artery aneursym. Myocardial infarction due to thrombus formation in dilated proximal CAF channels has been reported months 10 to years 11 after surgical closure of CAF.…”
Section: Discussionmentioning
confidence: 99%
“…Both approaches have very low reported morbidity and mortality, with the primary long‐term complication being residual flow through the fistula. Rare cases of intracoronary thrombosis and stenosis have been reported 5,10–12 . We report a neonate with congestive heart failure due to a large right coronary artery to right ventricular fistula (CA, CAVF Type B‐Distal, Origin‐RCA, Drainage‐RV, using the nomenclature of Dodge‐Khatami et al 13 …”
Section: Introductionmentioning
confidence: 99%
“…In general, open techniques may be associated with a reduced incidence of fistula recurrence compared to their endovascular counterparts. However, they keep the risks associated with median sternotomy, CPB, accidental closure of the main coronary vessels, as well as a small incidence of myocardial infarction 14 …”
Section: Discussionmentioning
confidence: 99%